Evaluation of Epidural Sensory Block by Thermal Stimulation, Laser Stimulation, and Recording of Somatosensory Evoked Potentials. Issue 2 (March 1996) - Zaric, Dusanka; Hallgren, Stig; Leissner, Lena; Nydahl, Per-Anders; Adel, Sven-Olof; Philipson, Lennart; Samuelsson, Lars; Leissner, Pehr; Axelsson, Kjell
Abstract : Background and Objectives: The existence of differential sensory block during epidural analgesia has been confirmed by some authors and disputed by others. This study attempts to elucidate this issue by using quantitative methods for evaluation of sensory block. Methods: A single epidural injection of 20 mL 0.5% bupivacaine with epinephrine was administered at the L1-T12 level in 11 male volunteers. Sensory block was evaluated by two qualitative (pinprick and light touch) and two quantitative methods (thermal stimulation with Thermotest [Somedic, Stockholm, Sweden] and argon laser stimulation). For measurement of motor block in the lower extremities and in the rectus abdominis muscle, quantitative methods were used. Sensory block was also assessed by somatosensory evoked potentials recorded during electrical and laser stimulation at the most cranial analgesic dermatome (loss of sharpness in pinprick perception) and the anesthetic dermatome L2 (loss of light touch perception). Results: The zone of anesthesia was smaller than the zone of any other investigated variable. The cranial spread of analgesia and motor block was lower than that of laser-assessed block. Partial block of laser perception and thermal perception lasted longer than analgesia and motor block. No consistent segmental or temporal differences were found between the Thermotest and laser methods. During epidural block, prolongation of latencies and reduction in amplitudes of somatosensory evoked potentials produced at the most cranial analgesic dermatome did not differ significantly from those produced at the anesthetic dermatome. Conclusions: No differential block of small nerve fibers was found during epidural analgesia by Thermotest and argon laser stimulation. Recording of somatosensory evoked potentials did not demonstrate significant difference between responses from the sites with most superficial and with most intense sensory block.